Systems Practice: How to Act in a Climate Change World - Ison, Ray (Springer Nature, 2010)
Builds the case for a systems praxiology Presents a range of ways of doing systems thinking and practice Contains extensive footnotes pointing to the sources and evidence of the authors' claims Demonstrates why systems thinking is needed in the governance of complex issues.